Application of Metroxylon sago waste in textile process - Shaari, Nazlina; Abd Rahman, Khairul Aidil Azlin (Korean Society of Design Science, 2014)
Sustainability is economic, social and environmental systems that make up the community in providing a healthy, productive, meaningful life for all community residents, present and future. The environmental profile of goods and services that satisfy our individual and societal needs was shaped by design activities. The integration of environmental aspect of product design, especially in textiles present much confusion surrounds the incorporation of environmental objectives into the design process. This paper explores the effective use of waste materials that can contribute to the development of more environmentally responsible practice in textile sector. It introduces key elements of the ecological approach and innovative ideas from waste to wealth. The paper focuses on the potential methods of utilizing sago residue as a natural color enhancer in natural dyeing process. It will discover the potential of waste materials to be fully utilized to attempt to make the production of that textile more environmentally friendly.